Study of Nutrient Concentration and Frequency of Drip Irrigation on Mustard Greens (Brassica rapa L.) Yields Using a Microcontroller - Rizky Harikurniawan; Sigit Soeparjono; Parawita Dewanti; Tri Wahyu Saputra (Universitas Khairun, 2023)
Plant nutrition and water provision are very important for plant growth and development. Nutrition can be done with AB mix nutrition with a certain concentration while the frequency of water can be controlled with a microcontroller. The purpose of this study was to examine the effect of various concentrations of AB mix nutrients and the frequency of irrigation water using a microcontroller on the yield of mustard greens. This research can be useful as a source of information related to the application of microcontroller sensors in the provision of appropriate AB mix water and nutrition for farmers and practitioners. The research design consisted of two treatments, namely the concentration of AB mix and the frequency of water administration with 3 repetitions. the concentration of AB mix nutrients given consisted of three variations, namely 750 ppm (D1), 1250 ppm (D2), and 1750 ppm (D3) while the frequency variations consisted of variations of 4x water administration (F1), 8x water administration (F2), and 12x water administration (F3). The volume of water has increased by three stages from the beginning of planting to harvest. The results showed that the AB mix concentration treatment showed a significant difference to plant fresh weight but not to other parameters. The frequency of water treatment also showed the same results as the nutrient concentration treatment and there was no interaction between the frequency of water treatment and the AB mix concentration. Furthermore, the best variation is the variation of nutrition 1750 ppm and the frequency of 8x watering.